2017
DOI: 10.1186/s12978-017-0433-z
|View full text |Cite
|
Sign up to set email alerts
|

The ‘heat’ goes away: sexual disorders of married women with female genital mutilation/cutting in Kenya

Abstract: BackgroundFemale genital mutilation/cutting (FGM/C) has been implicated in sexual complications among women, although there is paucity of research evidence on sexual experiences among married women who have undergone this cultural practice. The aim of this study was to investigate the sexual experiences among married women in Mauche Ward, Nakuru County.MethodsQuantitative and qualitative data collection methods were used. Quantitative data were obtained from 318 married women selected through multistage sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Women with FGM/C also suffer obstetric complications such as difficult in birthing process, obstructed and prolonged labour, tears and episiotomies [4,10,11]. Of note are sexual consequences related to the severed organs notably painful sexual intercourse, lack of orgasm, satisfaction and lubrication [12][13][14][15]. Additionally, women living with FGM/C present with anxiety, depression, post-traumatic stress disorder, and low self-esteem -the so called psychological impacts [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Women with FGM/C also suffer obstetric complications such as difficult in birthing process, obstructed and prolonged labour, tears and episiotomies [4,10,11]. Of note are sexual consequences related to the severed organs notably painful sexual intercourse, lack of orgasm, satisfaction and lubrication [12][13][14][15]. Additionally, women living with FGM/C present with anxiety, depression, post-traumatic stress disorder, and low self-esteem -the so called psychological impacts [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sexual experience and function of married women are negatively affected. This causes a poor sexual quality of life and nephrolithiasis [ 17 ]. Post-traumatic stress disorder commonly occurs in those women.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Sexual functioning can be affected as well, with studies showing FGC is linked to clinically significant and distressing problems with all three phases of the sexual response cycle-desire, arousal/excitement, and orgasm. 24 Studies have shown, for example, that FGC-affected women have reported higher rates of lack of sexual desire, 25 dyspareunia, 26,27 decreased orgasmic functioning, 28,29 and less sexual satisfaction 29,30 than women who have not been cut. However, it is important to note that women with FGC have sexual erectile tissues for sexual arousal and orgasm, 27 and some can and do experience pleasure and orgasm and report satisfying sexual lives.…”
Section: The Need For Comprehensive Medical Educationmentioning
confidence: 99%